Development of suitable mould and core refractory coating for foundry applications from locally available raw materials / Yahaya Ramli and Ramli Shafie - Ramli, Yahaya; Shafie, Ramli (1988)
Mould coatings have significance influence on the quality of the casting and therefore to foundries as well. Rough casting surfaces due to rough mould surfaces will require excessive machining work in order to produce a fine surface finished. This will result in the increasing of the cost of production of the components due to: i} Higher tooling cost. ii} Higher percentage of rejected parts. iii} Accuracy and tolerances are reduced. iv) Higher machining and setting time. The mould coatings already in use are imported either in form of a dry material or ready made mixtures and the material, are costly since the order must be in bulk (subjected to minimum order quantities}.